In vitro synthesis of IgG by peripheral blood lymphocytes in chronic liver disease. - Mutchnick, M G (1981)
In vitro IgG synthesis by peripheral blood mononuclear cells (PBM) from patients with chronic liver disease (CLD) was studied. In addition, the effect of pokeweed mitogen (PWM), polyadenylic-polyuridylic acid complexes (poly A:U) and thymosin fraction 5 on IgG synthesis was determined. Unstimulated cultures of PBM from patients with chronic active hepatitis (CAH) and alcoholic cirrhosis (AC) synthesized significantly higher quantities of IgG than the controls. Moreover, there was a direct correlation between serum IgG concentrations and the quantity of newly synthesized IgG in these unstimulated cultures. PWM, poly A:U and thymosin each stimulated increased IgG synthesis in the controls. While neither poly A:U nor thymosin enhanced IgG synthesis in patients with CLD, PWM increased IgG synthesis in CAH but not AC. These results indicate that spontaneous in vitro B cell synthesis of IgG is enhanced in CLD and may reflect antigenic stimulation in vivo.